COMPARISON OF DEXMEDETOMIDINE AND MIDAZOLAM FOR INTRA-OPERATIVE SEDATION IN TOTAL INTRAVENOUS ANESTHESIA (TIVA) IN CHILDREN UNDERGOING INGUINAL HERNIA REPAIR - FAROOQI , A; SADAF , S; BUTT , MR (Biological and Clinical Sciences Research Journal, 2024)
Effective intra-operative sedation is critical in pediatric surgeries to ensure patient comfort, hemodynamic stability, and efficient recovery. This study compared the efficacy and safety of dexmedetomidine and midazolam for intra-operative sedation in children undergoing inguinal hernia repair at Sheikh Zayed Medical College/Hospital, Rahim Yar Khan. Objective: To evaluate and compare sedation quality, hemodynamic stability, recovery time, and adverse events associated with dexmedetomidine and midazolam in pediatric patients undergoing inguinal hernia repair. Methods: This randomized controlled trial included 80 pediatric patients aged 2–12 years, randomly assigned to receive dexmedetomidine (Group D, n=40) or midazolam (Group M, n=40). Sedation depth was assessed using the Ramsay Sedation Scale (RSS) at intervals during surgery. Hemodynamic parameters, recovery time, and adverse events such as bradycardia, hypotension, oxygen desaturation, and apnea were recorded. Data were analyzed using SPSS version 26, with a p-value ≤0.05 considered statistically significant. Results: Sedation scores were significantly higher in Group D (mean RSS 4.5 ± 0.3) compared to Group M (3.8 ± 0.4, p<0.001). Group D demonstrated better hemodynamic stability, with a lower mean heart rate (85.2 ± 10.5 beats/min) than Group M (90.8 ± 11.2 beats/min, p=0.048), though with a slightly higher incidence of bradycardia (25% vs. 7.5%, p=0.032). Recovery time was significantly shorter in Group D (12.4 ± 3.2 minutes) compared to Group M (16.7 ± 4.1 minutes, p<0.001). Adverse events, including oxygen desaturation and apnea, were minimal and comparable between groups. Conclusion: Dexmedetomidine provides superior sedation, better hemodynamic stability, and faster recovery compared to midazolam in pediatric patients undergoing inguinal hernia repair, with minimal adverse events. These findings support the use of dexmedetomidine as a safer and more effective sedative alternative in pediatric surgical settings.